Identifikasi dan Perbandingan Kualitas Buah Mentimun (Cucumis sativus L.) Varietas Hercules dari Berbagai Kabupaten di Sumatera Selatan - Tanjung, Atha Loby; Dwi, Ni Made; Salsabila, Abelia; Gultom, Deni Saputra; Ryzanta, Aditya; Harun, M.Umar (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Tanjung, A. L., Dwi, N. M., Salsabila, A., Gultom, D. S., Ryzanta, A., Harun, M. U . (2024). Identification and comparison of quality of cucumbers (Cucumis sativus L) of the hercules variety from various districts in South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 937–945). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This research was carried out in August 2024. Cucumbers have distinctive shapes and characteristics ranging from color, size and taste so that there is a comparison of each region that cultivates cucumber plants. The aimed of this research was to determine the morphology and quality of cucumber fruit from various districts in South Sumatra, and also get information about the diversity of quality of cucumbers from various districts (Lahat, Muara Enim, Oku, Musi Rawas, Pagar Alam). This research method uses a sampling technique by randomly buying cucumbers from collecting traders. All five samples were prepared from various districts. All sampling cucumbers were analyzed at the Plant Physiology Laboratory, Unsri. The variables observed were volume, length, brightness of skin color, and quality grade of cucumber. All observed variables are analyzed non-statistically and compared with each other. Based on the results of diversity analysis of research data, the identification and comparison of the quality of cucumbers from various regions in South Sumatra gave rise to different assessments in each region. These differences show that cucumbers from Lahat have an average fruit length (23.7cm), and volume ( 32ml) as well as fruit grade A, and larger. Meanwhile, Muara Enim district has an average fruit length (23.2cm), and volume (87ml) and grade A. Oku district has an average fruit length (15cm), and volume (53ml) and grade C. Pagar Alam district has average fruit length (19.8cm), and volume (47ml), there is no grade, the Musi Rawas area has an average fruit length (18.5cm), and volume (64ml). This research shows that each region has different quality of cucumbers from each region which is caused by several factors including treatment and care for cucumbers, soil structure. As for suggestions from research.